2006
DOI: 10.1097/01.ogx.0000201923.84932.90
|View full text |Cite
|
Sign up to set email alerts
|

Menopausal Symptoms in Hispanic Women and the Role of Socioeconomic Factors

Abstract: The objective of this study was to assess differences in menopausal symptoms between postmenopausal (PM) Hispanic (H) and PM Caucasian (C) women. This was a prospective survey. Data from a convenience sample of 404 PM women (50% H, 50% C) were evaluated. Comparing H with C women, statistically significant differences (P < 0.05) in symptoms were noted with mood changes (76% H, 54% C), a decrease in energy (56% H, 36% C), palpitations (54% H, 26% C), breast tenderness (39% H, 28% C), memory loss (34% H, 22% C), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 14 publications
0
12
0
1
Order By: Relevance
“…59 Although the prevalence of HFs has increased in Japan, however, it is still lower than in most Western populations. 16,27,59 These findings, along with those from other studies, such as SWAN, 10,27,52,60 allude to an important observation that race=ethnicity may not independently explain HF prevalence, as no statistically significant association was found between ethnicity=race and HFs after adjustments for such covariates as lifestyle, BMI, smoking, menopausal status, and health-related quality of life.…”
mentioning
confidence: 64%
“…59 Although the prevalence of HFs has increased in Japan, however, it is still lower than in most Western populations. 16,27,59 These findings, along with those from other studies, such as SWAN, 10,27,52,60 allude to an important observation that race=ethnicity may not independently explain HF prevalence, as no statistically significant association was found between ethnicity=race and HFs after adjustments for such covariates as lifestyle, BMI, smoking, menopausal status, and health-related quality of life.…”
mentioning
confidence: 64%
“…23 One study found that Hispanic women living in the United States display more intense menopausal symptoms when compared with white women. 24 This difference persisted even after adjustment for socioeconomic level, therefore suggesting that ethnicity could be an independent risk factor predicting symptom intensity. We have recently reported data suggesting that severity of menopausal symptoms observed among Latin American women could be related to their indigenous origin.…”
Section: Discussionmentioning
confidence: 94%
“…9 In a study comparing vasomotor symptoms among white and Hispanic postmenopausal women, the two groups were reported to have no difference in the frequency of hot flashes and night sweats. 28 To date, few studies have described the difference in vasomotor symptoms between white and African American women during the postmenopausal period. Thus, the purpose of this study was to describe menopausal symptoms in a population of postmenopausal women and determine if there were any differences in symptomatology based on race.…”
Section: Introduction V Asomotor Symptoms Including Hot Flashesmentioning
confidence: 99%